Constitutional Review on the State’s Obligation to Provide Equal Access to Education in Indonesia - Firmanto, Fakhry; Sutrisno, Hafiz; Lubis, Arief Fahmi (Eastasouth Institute, 2025)
This study examines the constitutional obligation of the Indonesian state to guarantee equal access to education through a juridical normative analysis. Education in Indonesia is not only a social necessity but also a fundamental right enshrined in Article 31 of the 1945 Constitution, which mandates the government to organize and ensure an equitable national education system. The research uses a normative juridical approach by analyzing constitutional provisions, statutory regulations, and Constitutional Court decisions related to education and equality. The findings reveal that the Constitution provides a strong legal foundation for the right to education and equality before the law, supported by instruments such as Law No. 20 of 2003 on the National Education System and the constitutional requirement of allocating 20% of the national budget to education. However, challenges persist in implementation, including regional disparities, unequal resource distribution, and weak legal enforcement mechanisms. The study concludes that the realization of educational equality requires stronger legal accountability, equitable fiscal policy, and institutional consistency between constitutional norms and their practical execution. Strengthening constitutional integrity through judicial oversight and human rights–based education policies is essential to achieving the constitutional goal of “educating the life of the nation”.